1993
DOI: 10.1172/jci116720
|View full text |Cite
|
Sign up to set email alerts
|

Decreased 1,25-dihydroxyvitamin D3 receptor density is associated with a more severe form of parathyroid hyperplasia in chronic uremic patients.

Abstract: The resistance of parathyroid cells to 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) in uremic hyperparathyroidism is thought to be caused, in part, by a 1,25(OH)2D3 receptor (VDR) deficiency in the parathyroids. However, results of biochemical studies addressing VDR numbers in the parathyroids are controversial. Several studies have found VDR content to be decreased in the parathyroids of uremic patients and animals, while others have found no such decrease in the parathyroids of uremic animals.To clarify the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
265
0
19

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 563 publications
(296 citation statements)
references
References 29 publications
(17 reference statements)
12
265
0
19
Order By: Relevance
“…In that study, rats were fed a low-Ca diet and may have had parathyroid gland hyperplasia that could affect both Ca receptor and VDR content (17,18). Our results showing an effect of Ca on VDR are in agreement with Brown et al (9).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In that study, rats were fed a low-Ca diet and may have had parathyroid gland hyperplasia that could affect both Ca receptor and VDR content (17,18). Our results showing an effect of Ca on VDR are in agreement with Brown et al (9).…”
Section: Discussionsupporting
confidence: 89%
“…ferent. Russell et al (7) used vitamin D-depleted chickens, thus serum CTR and Ca levels were low and this would result in parathyroid hyperplasia, which may affect both Ca-sensing receptor (17) and VDR content (18). In our study, rats were not vitamin D-depleted.…”
Section: Discussionmentioning
confidence: 77%
“…Considering that all 14 patients in this study had a long history of hemodialysis, the majority of the parathyroidal lesions were naturally recognized as the N-type. N-type hyperplasia is usually present in patients with higher concentrations of intact PTH and the more severe bone symptoms [2]. Fukuda et al [2] reported that the clinically severe N-type parathyroid hyperplasia was associated with a reduced number of vitamin D receptors per unit of gland section compared with the mild D-type gland hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…N-type hyperplasia is usually present in patients with higher concentrations of intact PTH and the more severe bone symptoms [2]. Fukuda et al [2] reported that the clinically severe N-type parathyroid hyperplasia was associated with a reduced number of vitamin D receptors per unit of gland section compared with the mild D-type gland hyperplasia. Because the density of calcium sensing receptors is lower in the N-type glands, it is apparent that vitamin D receptor abnormalities in the parathyroid glands of patients with uremia play a role in the abnormal set point for calcium-regulated PTH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, elevated FGF23 activates the enzyme 24‐hydroxylase (CYP24), hydroxylating both 25(OH)D and 1,25(OH) 2 D. 24‐hydroxylase limits the amount of 1,25(OH) 2 D in target tissues both by producing 24,25(OH) 2 D (thus decreasing the availability of 25(OH)D for 1 hydroxylation) or by accelerating the catabolism of 1,25(OH) 2 D to 1,24,25(OH) 3 D resulting in calcitroic acid, which is biologically inactive 76, 77. CKD is also considered as a state of vitamin D resistance, because VDR expression in bone cells and in nodular parathyroid glands is reduced 78. Low 1,25(OH) 2 D levels also impair its binding to the VDR‐RXR complex 79, 80.…”
Section: Vitamin D Metabolism In Chronic Kidney Diseasementioning
confidence: 99%